Role of Beta Blockers in Ameliorating Sympathetic Storming in Isolated Traumatic Brain Injury - Amira Mohamed Ismail; Ibrahim Hablas; Ahmed Abdel Aziz Mohammed; Hazem Hossam E.L.din Abdel Hak (Egyptian Journal of Critical Care Medicine, 2022)
Abstract Background Early propranolol administration may compensate the catecholamines elevation that occur due to sympathetic hyperactivity during the first week post trauma and this can improve the survival rates among patients. Objectives Evaluating whether empiric early administration of propranolol in patients with moderate to severe traumatic brain injury (TBI) impacts outcomes. Methods This prospective case controlled study was conducted at the General ICU, Alexandria Main University Hospital among 100 patients who were diagnosed with isolated traumatic brain injury and were divided into two equal groups according to either received B-blockade or not. All the patients’ were submitted to full history taking, clinical diagnosis, and laboratory investigations. TBI was evaluated using Abbreviated Injury Scale (AIS) and post-rescuscitation Glasgow Coma Scale (GCS). Results The demographics’ and clinical characteristics’ including ICU stay and mechanical ventilation stay days of the studied groups showed no significant difference. There was no significant difference between the studied groups regarding the BB complications including hypotension, heart failure, and bradycardia. The mortality rates were significantly lower among patients who administrated BB. The incidence of undergoing craniectomy was significantly higher among group II than those who administrated BB. Conclusion The early administration of B-blockade among isolated traumatic brain injury patients could reduce the in hospital mortality rates and decrease the rates of craniectomy suggesting that BB are essential for survival and functional recovery among TBI patients.